Functional Characterization of CYP716 Family P450 Enzymes in Triterpenoid Biosynthesis in Tomato - Yasumoto, Shuhei; Seki, Hikaru; Shimizu, Yuko; Fukushima, Ery O.; Muranaka, Toshiya (Frontiers in Plant Science, 2017)
Triterpenoids are a group of structurally diverse specialized metabolites that frequently show useful bioactivities. These chemicals are biosynthesized from the common precursor 2,3-oxidosqualene in plants. The carbon skeletons produced by oxidosqualene cyclase (OSC) are usually modified by cytochrome P450 monooxygenases (P450s) and UDP-dependent glycosyltransferases. These biosynthetic enzymes contribute to the structural diversification of plant triterpenoids. Until now, many P450 enzymes have been characterized as triterpenoid oxidases. Among them, the CYP716 family P450 enzymes, which have been isolated from a wide range of plant families, seem to contribute to the triterpenoid structural diversification. Many CYP716 family P450 enzymes have been characterized as the multifunctional triterpene C-28 oxidases, which oxidize α-amyrin and β-amyrin to the widely distributed triterpenoids ursolic and oleanolic acids, respectively. Tomato (Solanum lycopersicum) is one of the most important solanaceous crops in the world. However, little information is known regarding its triterpenoid biosynthesis. To understand the mechanism of triterpenoid biosynthesis in tomato, we focused on the function of CYP716 family enzymes as triterpenoid oxidases. We isolated all six CYP716 family genes from the Micro-Tom cultivar of tomato, and functionally characterized them in the heterologous yeast expression system. The in vivo enzymatic assays showed that CYP716A44 and CYP716A46 exhibited the ordinary C-28 oxidation activity against α-amyrin and β-amyrin to produce ursolic and oleanolic acids, respectively. Interestingly, one CYP716E subfamily enzyme, CYP716E26, exhibited the previously unreported C-6β hydroxylation activity against β-amyrin to produce a rare bioactive triterpenoid, daturadiol (olean-12-ene-3β,6β-diol). To determine the roles of the CYP716 family genes in tomato triterpenoid biosynthesis, we analyzed the gene expression and triterpenoid accumulation patterns in different plant tissues by performing the quantitative real-time polymerase chain reaction (qPCR) and gas chromatography-mass spectrometry (GC-MS) analyses, respectively. High levels of the CYP716A44 gene expression and the accumulation of C-28-oxidized triterpenoids, ursolic acid and oleanolic acid were observed in the roots, indicating a significant contribution of the CYP716A44 gene in the triterpenoid biosynthesis in tomato. Thus, our study partially elucidated the mechanism of triterpenoid biosynthesis in tomato, and identified CYP716E26 as a novel C-6β hydroxylase for its subsequent use in the combinatorial biosynthesis of bioactive triterpenoids.